2018
DOI: 10.1097/pr9.0000000000000677
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 inducer and carbon monoxide–releasing molecule enhance the effects of gabapentinoids by modulating glial activation during neuropathic pain in mice

Abstract: Introduction:Neuropathic pain is one of the most difficult-to-treat symptoms. Although gabapentinoids are classified as first-line drugs, they have only modest efficacy.Objectives:The aim of this study was to investigate whether treatment with the heme oxygenase-1 (HO-1) inducer cobalt protoporphyrin IX (CoPP) or the carbon monoxide–releasing molecule tricarbonyldichlororuthenium (II) dimer (CORM-2) can enhance the antinociceptive effects produced by gabapentinoids in mice with neuropathic pain.Methods:Neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…SnPP was administered 30 min after 5-fluoro-2-oxindole injection and animals were tested 30 min after SnPP injection ( n = 6 animals per group). The dose of SnPP was selected in accordance with other studies [ 18 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…SnPP was administered 30 min after 5-fluoro-2-oxindole injection and animals were tested 30 min after SnPP injection ( n = 6 animals per group). The dose of SnPP was selected in accordance with other studies [ 18 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…57,59 Other studies have further shown that CORM-2 increases the analgesic effects of buprenorphine 51 and that both CoPP and CORM-2 improve the antiallodynic actions of the gabapentinoids, pregabalin, and gabapentin, by increasing HO-1 and Ca 2+ channel α2δ1 subunit gene expression and inhibiting microglial activation and the overexpression of TNF-α in the spinal cords of animals with neuropathic pain. 18 The Nrf2 transcription factor modulates oxidative stress and the inflammatory and pronociceptive pathways in the peripheral and central nervous systems. 140,141 A crucial factor for the antioxidant activity of Nrf2 is the modulation of the transcription of numerous genes that encode antioxidant and detoxifying enzymes, such as HO-1, NQO1, superoxide dismutase 1, and glutathione peroxidase.…”
Section: Activation Of Ho-1 and Carbon Monoxide Modulates The Antinmentioning
confidence: 99%
“…In the last years, several studies have evaluated the anti-inflammatory and antinociceptive effects of carbon monoxide as well as those produced by activators of inducible heme oxygenase 1 (HO-1) or the nuclear factor-2 erythroid factor-2 (Nrf2) transcription factor alone or in combination with other analgesic compounds in different preclinical pain models. [11][12][13][14][15][16][17][18][19][20][21][22] In this review, we examine, in chronological order, the results obtained by us and other research groups regarding the effects of HO-1 and carbon monoxide in pain, their mechanisms of action during chronic pain, and their effects on the antinociceptive actions of opioids, cannabinoids, and other analgesics during chronic pain. We also revised the effects of Nrf2 transcription factor activators in pain, their effects in the analgesic actions of opioids and cannabinoids as well as on the emotional disorders accompanying chronic pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemin (ferriprotoporphyrin IX), a derivative chemical from heme, was used as a representative of heme-induced HO-1 expression 35,36 . Application of cobalt protoporphyrin IX (CoPP) as HO-1 inducer and tin protoporphyrin IX (SnPP) as HO-1 inhibitor are widely used in previous researches 29,30,37,38 . Hemin and CoPP induced HO-1 mRNA expression as expected (Fig.…”
Section: Presence Of Hemin and Induction Of Ho-1 Decreased Ifn-γ And mentioning
confidence: 99%